Role of socio-economic and institutional component in the formation and functioning of agricultural holdings in Ukraine - Dorosh, O.; Kupriyanchyk, I. (Land Management, Cadastre and Land Monitoring, 2017)
Stages of formation and development of agro-industrial companies - holdings in Ukraine. It was determined that the formation of agro-industrial companies in Ukraine affect the following processes: 1) because of the concentration of land increased production of agricultural products; 2) the use of new technologies in agriculture; 3) integration of production with the subsequent processing of agricultural products; 4) establishment of integrated and export-oriented structures; 5) attract loans from international financial organizations. Since 2015 restricted access to credit, slowly developing technologies held several agricultural holdings default. It is noted that this development is an indication that the formation and operation of agricultural holdings occurred spontaneously, without public exposure, proper institutional and socio-economic support rural development. Analyzed and structured information on the concentration of land in the top 100 agricultural holdings Ukraine and found that 67% of arable land is concentrated in agricultural companies area over 100 thousand hectares. 18% - 50 000 - 100 000 thousand. Ha and 15% - from 10 000 - 50 000 thousand. hectares of land. In addition, existing today agricultural holdings have their management in a territory that spans from 15 to 22 regions of Ukraine (45%), 43% - from 6 - 15 regions, 9% - from 2 - 5% and only 3% are concentrated in one area covering between 1 and 2 areas. It has been proved that most agricultural companies are registered in offshore zones and cities in Ukraine in order to minimize taxes. A mechanism to introduce taxes not the place of registration, and the location of their business operation, ie in rural areas. This will allow local communities to accumulate funds local budgets for the development of social infrastructure. On the basis of research singled out the advantages and disadvantages of holdings and proved illusory benefits of large-monopoly and monoculture agricultural business compared to other types of business entity. For the proper functioning of Ukraine asked to create adequate institutions in the provision of priority social and economic components.component. It is recommended to ensure a clear demarcation of farms and agricultural holdings in law to provide standards for the size of agricultural land use (enterprises in size from 500 to 5,000 hectares - the average farms from 5 000 to 10 000 hectares - large farms and 10 000 50 000 ha - agricultural holdings, from 50 000 to 100 000 - mehaholdynhy and more than 100 000 - hiperholdynhy. Keywords: agricultural holdings, the agricultural enterprises, the institutional component, social economic development.